2015
DOI: 10.1097/01.j.pain.0000460339.23976.12
|View full text |Cite
|
Sign up to set email alerts
|

Exercise therapy normalizes BDNF upregulation and glial hyperactivity in a mouse model of neuropathic pain

Abstract: Treatment of neuropathic pain is a clinical challenge likely because of the time-dependent changes in many neurotransmitter systems, growth factors, ionic channels, membrane receptors, transcription factors, and recruitment of different cell types. Conversely, an increasing number of reports have shown the ability of extended and regular physical exercise in alleviating neuropathic pain throughout a wide range of mechanisms. In this study, we investigate the effect of swim exercise on molecules associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
102
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(114 citation statements)
references
References 87 publications
11
102
0
1
Order By: Relevance
“…They may also explain, in part, the fact that exercise is beneficial for chronic pain patients because it reduces pain perception and also exhibits antidepressant and cognition-enhancing effects (Ambrose and Golightly, 2015). Interestingly, exercise increases BDNF expression in the hippocampus, but suppresses BDNF production in the spinal dorsal horn (Mattson, 2012;Almeida et al, 2015). It will be of considerable interest to determine whether there are roles for microglia and TNF-␣ in these beneficial effects of exercise on chronic pain.…”
Section: Discussionmentioning
confidence: 99%
“…They may also explain, in part, the fact that exercise is beneficial for chronic pain patients because it reduces pain perception and also exhibits antidepressant and cognition-enhancing effects (Ambrose and Golightly, 2015). Interestingly, exercise increases BDNF expression in the hippocampus, but suppresses BDNF production in the spinal dorsal horn (Mattson, 2012;Almeida et al, 2015). It will be of considerable interest to determine whether there are roles for microglia and TNF-␣ in these beneficial effects of exercise on chronic pain.…”
Section: Discussionmentioning
confidence: 99%
“…They may also explain, in part, the fact that exercise is beneficial for chronic pain patients because it reduces pain perception and also exhibits antidepressant and cognition-enhancing effects (Ambrose and Golightly, 2015). Interestingly, exercise increases BDNF expression in the hippocampus, but suppresses BDNF production in the spinal dorsal horn (Mattson, 2012;Almeida et al, 2015). It will be of considerable interest to determine whether there are roles for microglia and TNF-␣ in these beneficial effects of exercise on chronic pain.…”
Section: Discussionmentioning
confidence: 99%
“…1,6,7,1215,18,31,34,42,54,60 Several studies have reported that neuroimmune signaling, processes that subserve neuropathic pain after nerve injury, 2,21 is suppressed in the neuraxis of rodents exercised after injury. For example, expression of activation markers for microglia (Iba1, CD11b) and astrocytes (GFAP) is decreased in the spinal dorsal horn, 1,6,15,31,42 while pro-inflammatory cytokines tumor necrosis factor and interleukin-1β (IL-1β) are downregulated in the brainstem and sciatic nerve. 7,12,13 Such pro-inflammatory cytokines are produced by reactive macrophages, microglia, and astrocytes, and increase neuroexcitability in nociceptive pathways (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…2,21,74 Brain derived neurotrophic factor (BDNF) expression is also attenuated in the dorsal root ganglia (DRG) and spinal dorsal horn, and potassium-chloride cotransporter (KCC2) expression is restored in the spinal dorsal horn in exercised rodents. 1,14,42 This pro-nociceptive axis induces disinhibition following downregulation of KCC2 by P2X4 receptor-dependent BDNF release from microglia. 17,66,67 …”
Section: Introductionmentioning
confidence: 99%